A bioassay of long‐term stockpiled salvaged soil amended with biochar, peat, and humalite. Issue 1 (6th July 2020) - Laskosky, Jorden D.; Mante, Afua A.; Zvomuya, Francis; Amarakoon, Inoka; Leskiw, Leonard
Abstract: Long‐term stockpiling of soil salvaged from oil sands operations often leads to the deterioration of soil quality and poor reclamation results for disturbed land. This study assessed the efficacy of organic amendments in improving the quality and productivity of long‐term stockpiled salvaged soil in Canada's Alberta oil sands region (AOSR). Dry soil samples (4.2 kg) from a 24‐yr‐old stockpile were placed into 5‐L pots and amended with biochar, humalite, peat, and 50:50 mixtures of biochar and peat (BCP) and biochar and humalite (BCH) at rates corresponding to 0, 6.55, 13.1, and 26.2 g C kg −1  soil. The pots were seeded with barley ( Hordeum vulgare L.), fertilized, and placed in a growth chamber. Plants were allowed to grow for three crop cycles of 45 to 59 d each and harvested at the end of each cycle. Results showed that biochar and peat increased dry matter yield (DMY) by 38 and 40%, respectively, compared with the unamended soil. Humalite produced the highest N and P concentrations in plant tissue, but this did not translate to an increase in DMY. Biochar and peat offer the greatest promise for improving the productivity of long‐term stockpiled salvaged soil, thereby enhancing the success of reclamation of disturbed sites.